A description of the Humanitarian Sense of the 5th year students of The School of Arts and Social Sciences of the University of El Salvador seen through the students´ participation in Social Programs during the first Semester of 2018 - Guerra Mejía, Valeria Madai
A description of the humanitarian Sense of the students of the 5th year of The School of Arts and Social Sciences of the University of El Salvador seen through the student's participation in Social Programs during the first Semester 2018”. The students of the fifth year of The School of Arts and Social Sciences are expected to follow the humanitarian approach of the school in order to contribute to the resolution of the current social problems by participating in humanitarian activities in favor of the development of Salvadorans in general. Therefore, the purpose of this research work was: to describe how students of the School of Arts and Social Sciences get involved in humanitarian programs during their studies. A survey was conducted to collect the necessary information; a questionnaire containing open and close-ended questions about the participation of students in humanitarian projects, and factors that might being enhance a committed way of thinking in pro of the developing of the society was used . The obtained results provided the researchers with information about what the main factors that influence the students’ humanitarian behavior are: political, religious, familial, or/and the philosophy of the University. At the same time, the results also showed the humanitarian activities in which students have been involved during their studies, and how this participation has benefited or affected them in their professional and personal life. Besides, the research makes reference to the factors that might be hindering the student’s participation. The School of Arts and Social Sciences of the University of El Salvador can use the results of this research to evaluate the current participation in humanitarian projects of the students, and if the philosophical framework stated is being attained